2011
DOI: 10.1016/j.jcgg.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age and metabolic disorders in the population of Bali

Abstract: a b s t r a c tBackground/Purpose: The purpose of this study is to examine the association between age and metabolic disorders in the population of Bali. Method: A cross-sectional study was conducted on metabolic syndrome (MS) as defined on the basis of recommended parameters for diagnosis of the syndrome in the population of seven villages of Bali comprising six villages and one suburban area. At least three of the five parameters must be present for the diagnosis. Three hundred ten elderly people aged 60 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 19 publications
3
24
0
7
Order By: Relevance
“…This study was part of the metabolic disorder study done in Bali, where DNA samples were available [33]. The subjects were recruited by random sampling from either urban (278 subjects) or rural (325 subjects) settlements, and then stratified for large villages and sub-villages.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of the metabolic disorder study done in Bali, where DNA samples were available [33]. The subjects were recruited by random sampling from either urban (278 subjects) or rural (325 subjects) settlements, and then stratified for large villages and sub-villages.…”
Section: Methodsmentioning
confidence: 99%
“…The peak prevalence of diabetes can be found in the age group of 65-74 years with 15.7% in men and 10.4% in women (Shelton, 2006). The study by Suastika et al (2011) on Bali population showed that the prevalences of IFG and T2DM were higher in the elderly than in the younger age group, i.e. nearly two-fold and more than two fold, respectively (Figure 2).…”
Section: Age and Type 2 Diabetes Mellitusmentioning
confidence: 98%
“…The Rotterdam study that enrolled 574 non-diabetic elderly population showed that insulin correlated strongly and significantly with C-reactive protein (CRP), -1-antichymotrypsin, interleukin (IL)-6 and soluble intercellular adhesion molecule-1, indicating that insulin resistance is an integral part of inflammation (Hak et al, 2001). A study by Suastika et al (2011) on the population of Bali, Indonesia, has showed a tendency of increasing frequency of metabolic syndrome and its components with increasing age (Table 1). A study on the elderly by Zambon et al (2009) found that metabolic syndrome was associated with increased mortality by various causes (HR 1:41) and mortality from CVD (HR 1.60).…”
Section: Age Insulin Resistance and Metabolic Syndromementioning
confidence: 99%
“…A study by Suastika et al revealed that the prevalence of MetS and central obesity increased with age, peaking at 50-59 years and decreasing in the older age group. 7 This finding might add fuel to the prevailing controversy about the relationship between age, underweight, and CHD. A study of coronary artery disease (CAD) after prenatal exposure to the Dutch famine revealed an earlier onset of CAD among individuals conceived during the famine, suggesting that maternal nutrition in early gestation may play a role in the onset of CAD.…”
Section: Discussionmentioning
confidence: 92%